2014
DOI: 10.1038/ctg.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of 25-Hydroxy Vitamin D are Independently Associated with the Risk of Bacterial Infection in Cirrhotic Patients

Abstract: OBJECTIVES:Low levels of vitamin D are associated with a higher mortality in cirrhotic patients, but the role of this deficiency is still unknown. The purpose of this study was to assess the levels of vitamin D in cirrhotic patients with and without bacterial infection.METHODS:25-hydroxy (25-OH) vitamin D was assessed by immunoassay in 88 patients hospitalized in our hepatology unit.RESULTS:The causes of cirrhosis were mainly alcohol (70%), hepatitis C (10%), or both (9%). Infections (n=38) mainly included bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 57 publications
0
39
0
2
Order By: Relevance
“…A deleterious impact of the lack of vitamin D on the immune system is possible during severe chronic liver diseases (Iruzubieta et al, 2014). We have previously shown, in a cohort of mainly alcoholic cirrhotic patients, that a severe deficiency in 25-OH vitamin D was associated with an increased risk of bacterial infection independently of the Child-Pugh score (Anty et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A deleterious impact of the lack of vitamin D on the immune system is possible during severe chronic liver diseases (Iruzubieta et al, 2014). We have previously shown, in a cohort of mainly alcoholic cirrhotic patients, that a severe deficiency in 25-OH vitamin D was associated with an increased risk of bacterial infection independently of the Child-Pugh score (Anty et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D insufficiency was not an independent risk factor for mortality in logistic regression analysis (OR= 1.8 95% CI 0.554-5.863, p = 0.328), thus Vitamin D insufficiency may be a helper but not a real risk factor for mortality Significant association between Vitamin D levels and illness severity on admission: SOFA Score: insufficiency: 8 (6-11), sufficiency: 6 (4-9), p = 0.005 APACHE II Score: insufficiency: 24 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) Multiple-regression model using variables that significantly correlated with admission FIM score (age, grip strength, and body weight): only serum 25OHD was a significant contributor (p = 0.02) to the multiple r value (multiple r = 0.42, p = 0.001).…”
Section: Prevalence Of Vitamin D Deficiency and Insufficiencymentioning
confidence: 97%
“…23 The incidence of bacterial infections in cirrhotic patients has been found to not be associated with vitamin D levels. 22 Only one study looked at intensive care unit (ICU) admission rates and found a significant inverse relationship with vitamin D levels. 19 An investigation of a correlation between vitamin D levels and length of hospital stay showed contradicting results.…”
Section: Secondary Endpoints: Infections and Other Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that a low level of vitamin D was independently associated with an increased risk of bacterial infection in patients with cirrhosis (10); however, the exact mechanism is unclear.…”
mentioning
confidence: 98%